Intraoperative hemodynamic management during pancreatoduodenectomy: an analysis of 525 patients - Dietrich, Maximilian; Hölle, Tobias; Piredda, Mattia; Feißt, Manuel; Rehn, Patrick; Forst, Maik von der; Fischer, Dania; Hackert, Thilo; Larmann, Jan; Michalski, Christoph; Weigand, Markus A.; Loos, Martin; et al. (Langenbeck's archives of surgery, 2025)
Optimization of perioperative hemodynamic management during major pancreatic surgery can reduce postoperative complications.
Gesehen am 01.10.2025